Stocking density effects on turkey hen performance to 11 weeks of age - S. Jhetam; K. Buchynski; T. Shynkaruk; K. Schwean-Lardner (Poultry Science, 2022)
ABSTRACT: Stocking density (SD) affects economic return for turkey production and can impact performance parameters. In this study (2 experimental blocks), Nicholas Select hens (n = 3,550 poults/block) were randomly placed in 1 of 4 SD treatments of 30, 40, 50, or 60 kg/m2 in open rooms (67.5 m2) with 4 replications per treatment. Feeder and drinker space were equalized on a per bird basis. Air quality was measured, and ventilation was adjusted to equalize ammonia and carbon dioxide levels across all rooms. Group BW and feed consumption were measured on d 0 and wk 3, 5, 8, and 11. BW gain and mortality corrected feed-to-gain ratio were calculated. Mortality and culls were recorded daily and necropsied for cause of death. At wk 8 and 11, flock uniformity was evaluated (30 birds/replicate). Data were analyzed using regression analyses in SAS 9.4 (Proc Reg for linear regression and Proc RSReg for quadratic regression; SD as independent variable). An ANOVA was performed for air quality (Proc Mixed; SAS 9.4) and a Tukey's range test was used to separate means. Differences were considered significant when P ≤ 0.05. Carbon dioxide and ammonia were consistent across treatments for both blocks. At wk 11, BW decreased linearly as SD increased (P = 0.05). There was a tendency for overall BW gain to decrease linearly as SD increased (P = 0.06). Feed consumption decreased as SD increased during wk 8 to 11 (linear; P < 0.01) and from wk 0 to 11 (quadratic; P = 0.04). SD had no impact on feed efficiency, mortality, or uniformity. Total aggression related mortality and culls were highest in the 30 kg/m2 treatment (linear; P = 0.02). A brief economic analysis was performed utilizing commercial poult and feed costs and income at marketing. Net room income increased as SD increased (linear; P < 0.01). The results indicate that high SD negatively impacted turkey hen final BW and feed consumption, but no effect was observed on feed-to-gain ratio, percent mortality, or uniformity.